(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2023)
This research clarifies the peculiarities characterizing the genre of “short stories with a thesis” in the literary works by B. Prus. It reveals the specifics of the author’s strategy showing the way of composing the main structural elements of the text at the form level. This paper demonstrates that the theses in the genre structure of short stories by B. Prus indicated the writer’s attempts to write his works according to a clearly planned compositional principle. It is noted that the thesis served as a starting point due to which B. Prus initiated and further explained or reinforced important fact-events from the lives of the characters. The purpose of the research is to study the structural peculiarities of such a genre as “short stories with a thesis” by means of component analysis. It has been noticed that the writer built up the plot on the fertile foundation of important emotional nodes that formed the basis of the plot of the short story. It should be noted that in addition to the thesis the writer formulated a so-called “postskriptium” at the end of his short stories, which allowed him to explain to the reader important truths that the B. Prus embodied in the works. This is a defining feature of his short stories with a thesis, as the judgment he formulated at the beginning of the short story was necessarily proven and confirmed during the plot development. Due to the component analysis, it has been found that an important technique in the development of the plot of the short story is the narrator’s internal thoughts, with the help of which the plot of the short story unfolds gradually. It should be stated that B. Prus used the following techniques: the use of memory, retrospection, contrast, internal thoughts of the character. All of these methods slow down the entire development of the plot as much as possible, detaining the reader’s attention on important moments of actions and actions of the characters. In this way the writer tried to accumulate a number of emotions of the recipient in order to force him to thoughtfully read the text of the literary work. The unexpected development of the plot is also a specific peculiarity of the novel and it is achieved by means of using unpredicted twists, which significantly affect the development of the plot.